Combined racing skiers' competitive fitness typing at sport mastery excellence stage - Farbey, V. V.; Dunaev, K. S. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to profile the sport excellence process in combined skiing events versus the classified competitive fitness rates. The study found that the high competitive success is normally achieved by the combined skiers by the age of 20-22 years conditional on their skiing careers starting from 9-10 years of age as verified by the track record data of the Winter Olympics, all-Russian and World champions and finalists. It was also found that at least 11-13 years of training are required for a combined skier to reach the top mastery level. Regardless of the special skiing events the athletes specialize in, they normally go through virtually the same age-specific stages of the training process showing virtually the same competitive success rates at every stage. Analysis of the competitive success rates of the combined skiers versus their sport rankings made it possible to profile their competitive successes. The competitive accomplishments in specific sports of the combined skiing events and the relevant contributions to the final competitive success were used as a competitive fitness rating criterion. It was found that the sport excellence process of the combined skiers is to be designed so as to build up the so-called universal type of competitive fitness.